Application of Ratio Derivative Spectrophotometry for Simultaneous Determination of Naphazoline and Antazoline in Eye Drops - R. Hajian; N. Shams; I. Kaedi (E-Journal of Chemistry)
Ratio derivative spectrophotometrie method has been developed for the simultaneous determination of naphazoline (NAP) and antazoline (ANT) at micromolar levels in Britton Robinson buffer (pH 9) medium. In this method the overlapping spectra of naphazoline and antazoline were well resolved by making use of the first-derivative of the ratios of their direct absorption spectra. The derivative ratio absorbances of naphazoline and antazoline were measured at 227.2 and 235 nm, respectively for their quantification. The method is simple, fast and does not require separation of naphazoline and antazoline. Another salient feature of the method is that simultaneous standard additions of both analytes permitted to resolve matrix effect and quantification at a unique standard addition plot. Naphazoline and antazoline were determined in the concentration range of 10-150 μmol L-1 (NAP/ANT ratio varying from about 10 to 150) in the same aliquot with a precision and accuracy of about 1.7% and 1.8%, respectively. The recommended procedure was successfully applied for analysis of naphazoline and antazoline in eye drops.